Use of ARIAS Model (Assurance, Relevance, Interest, Assessment, Satisfaction) on Speech Learning - Bonafetura Niamonio Ziliwu; Wecan Kartika Hidayati Gea; Arozatulo Bawamenewi; Agung Harapan Harefa (Journal of Social Science Utilizing Technology, 2024)
Background. The effectiveness of oral corrective feedback (OCF) in language learning is influenced by learners’ comprehension and response to various OCF techniques. Therefore, it is essential for teachers to consider learners’ preferences for OCF strategies. Purpose. this study aims to investigate the use of ARIAS Model on speech learning. This research will explore the effectiveness of this approach in helping learners overcome challenges in public speaking and improve their speaking skills with more confidence and conviction. Method. This research used a qualitative method with a descriptive approach. Data collection techniques included interviews, observations, and questionnaires filled out by 21 students. Results. The results showed that the use of the ARIAS model significantly improved students’ clarity (85%), intonation (80%), and expression (90%) in speech. In addition, 95% of students gave positive responses to the ARIAS model, indicating its acceptance and effectiveness in speech learning. Conclusion. This study concludes that the ARIAS model is a comprehensive and effective approach to develop public speaking skills, help students overcome psychological barriers, and improve their speech skills with more confidence and convincing. However, technical challenges such as technological infrastructure must be overcome to ensure optimal implementation. The findings support the importance of integrating the ARIAS model in the Indonesian language learning curriculum to improve students’ communication skills.